Changes in the cervicovaginal microbiota composition of HPV16‐infected patients after clinical treatment - Chao Li; Zhenbo Zhang; Yixia Yang; Hong Liao (Cancer Medicine, 2022)
Abstract Background High‐risk human papillomavirus (hrHPV) infection is a key factor that alters cervicovaginal microbiota patterns and causes cervical intraepithelial neoplasias (CINs) or even cervical cancer. Although local excisional treatment can clear hrHPV infection and restore the cervicovaginal microbiota, it is unclear which cervicovaginal microbiota represents recovery. Our objective was to describe the cervicovaginal microbiota before and after treatments and to assess the association between the microbiota and HPV persistence. Results A cohort of 91 participants was classified into four groups (healthy control women and HPV16‐infected women with CIN I, CIN II/III, and squamous cell carcinoma [SCC]). Endocervical swabs were collected 3 months prior to treatment and at 3 months post‐treatment for bacterial 16S rRNA gene pyrosequencing and for HPV DNA testing. There was an increase in the number of Lactobacillus bacterial species present after the clinical treatments, and the community state type (CST) profiles were shifted from dysbiotic CSTs II and IV to Lactobacillus‐dominated CSTs I and III. Specifically, the composition of Geobacter and Prevotella before treatment and Lactobacillus secaliphilus after treatment might have been related to CIN I, the composition of Burkholderia before treatment and Lactobacillus iners after treatment might have been related to CIN II/III, and the composition of Atopobium and Aerococcus before treatment and Bacilli after treatment might have been related to SCC. Further functional predictions revealed that the composition differences were linked to infectious disease‐ and cancer‐related genes. Conclusion Our study provides an illustration of the changes in CSTs and the cervicovaginal microbiota before and after HPV16 clearance in each disease state.